2020
DOI: 10.1080/08039488.2020.1833983
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians’ experiences on patients’ demands and shared decision making in Finnish specialized mental health care

Abstract: Purpose: Psychiatric patients' awareness of treatments options and their possibilities to influence their care has increased. For the clinicians, the management of evidence-based care, as well as organizational and resource aspects, set different goals for the clinical encounter. In this article we are focusing on the clinicians' experiences and ask: How do the clinicians view situations in which there is a conflict between patients' individual needs and goals and other aspects in decision-making? Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…There is also room for improvement in service users’ preferences regarding treatment, informed consent, and facilities (standard score 2.4/3). A recent interview study among Finnish clinicians working in psychiatric care concluded that there seems to be a shift from paternalistic treatment decisions towards shared decision making (SDM) and patient-centered care [ 50 ]. From the viewpoints of service users and their families, these improvements are still modest [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is also room for improvement in service users’ preferences regarding treatment, informed consent, and facilities (standard score 2.4/3). A recent interview study among Finnish clinicians working in psychiatric care concluded that there seems to be a shift from paternalistic treatment decisions towards shared decision making (SDM) and patient-centered care [ 50 ]. From the viewpoints of service users and their families, these improvements are still modest [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%